Statistical assessment of environmental noise generated by road traffic - Jagniatinskis, Aleksandras; Fiks, Boris; Mickaitis, Marius (Transport, 2011)
The necessity to check requirements for sound insulation of new building façades against outdoor noise and for estimating noise pollution of the residential area comprise the assessment of environmental noise taking in situ measurements that are mainly carried out under the standardized method presented in the EU directives and Lithuanian legislation. For these estimations, annual composite daily equivalent sound pressure level Lden becomes obligatory. When the value of this descriptor is determined from measurements, it is relevant to reasonably reduce a time interval of the performed measurement. The possibilities of determining the noise level Ld ,12h of the day (12h) undertaking annual Lden assessment making short-term (15÷60 min.) measurements is dealt in this work. In this way, the sensitivity of the set of statistical descriptors to variations in sound pressure levels was investigated. The paper proposes that the obtained instantaneous A-weighted sound pressure levels with F (fast) time weighting histogram of distribution density may be used for characterizing noise pollution in the sites. When traffic noise emitted from arterial town roads with stationary traffic takes a dominating position, the form of these histograms is close to normal distribution density with corresponding statistical parameters: average, standard deviation, asymmetry coefficient and percentiles. The experimental measurements have established that an asymmetry coefficient and an introduced descriptor– the rank of percentile Neq% are the most sensitive to noise variations. The last one is more preferable due to its exclusive relationships with an equivalent level– the corresponding value of this rank of percentile PNeq that coincides with the equivalent level of the measured time interval. It has been found that the introduced descriptor Neq is very sensitive for indicating the dissimilarity of environmental noise (the presence of a casual impulse or high energy noise events). In-situ measurements of the vicinity of roads with intensive traffic in Vilnius City, where stationary urban traffic noise is dominating, indicate that the values of Neq rank obtained during short-term (15÷60 min) intervals in the period from7:00 to 19:00 are stable and vary from 69% to 74%. When non-stability occurs, a significant increase in the values of this descriptor may be applied as criteria for indicating noise events other than traffic noise and may be used for determining the interval limits of short-term stationary measurement. First Published Online: 12 Apr 2011